Pragmatic Competence and Failure in Second and Foreign Language Teaching - Fanukh Abbas, Chassib (International Journal of Psychosocial Rehabilitation, 2020)
Although practical efficiency an essential part of L2 learners’ ability, L2 teachers usually neglect practical because of the difficulty that underlies its teaching. As for teaching, they concentrate part of the language, therefore; that lack the practical efficiency for those L2 students leads to practical failure and may also lead to miscommunication for those students. Guidance is provided to encourage those who want to learn into their lessons and to prevent their learners from making those mistakes, some tutors allow their students to break the rules to make the pragmatic judgment, but this cannot be done unless students know the difference between practical linguistics and socio practical failures (Ibid). Davies (1986: 121) supports this idea when he indicates that learners should be enabled to choose to be either polite or impolite rather than being taught to be polite. Dash (2004: 12) emphasizes that openness to different practical performances is the efficiency with these different cultivational, and public groups are something to be considered about; likewise, a way that is free of stereotypical judgments.